T cells specific for post-translational modifications escape intrathymic tolerance induction - Bruno Raposo (Nature Portfolio, 2018)
Post-translational modifications are associated with autoimmune diseases but definitive evidence of their contribution to escape from central tolerance mechanisms is needed. Here, the authors show that T cells specific for post-translational modifications of type II collagen escape intrathymic tolerance induction in a mouse model of rheumatoid arthritis.